Mothers at Work: How Mandating Paid Maternity Leave Affects Employment, Earnings and Fertility - Esther Mirjam Girsberger; Lena Hassani Nezhad; Kalaivani Karunanethy; Rafael Lalive (Institute of Labor Economics (IZA), 2021)
In July 2005, Switzerland introduced the first federal paid maternity leave mandate, offering 14 weeks of leave with 80% of pre-birth earnings. We study the mandate's impact on women's employment and earnings around the birth of their first child, as well as on their subsequent fertility by exploiting unique, rich administrative data in a difference-in-differences set-up. Women covered by the mandate worked and earned more during pregnancy, and also had temporarily increased job continuity with their pre-birth employer after birth. Estimated effects on other labor market outcomes are small or absent, and all dissipate by five years after birth. The mandate instead persistently increased subsequent fertility: affected women were three percentage points more likely to have a second child in the next nine years. Women living in regions that had greater early child care availability experienced a larger increase in subsequent fertility following the mandate, suggesting that child care complements paid maternity leave in helping women balance work and family.
Keywords: J1; J2; 330; female labor supply; maternity leave; return-to-work; earnings; fertility